KEY TAKEAWAYS REGARDING THE INTENTIONS OF RUSSIA’S MEDIA CAMPAIGNS - Julia Davis (The Journal of Intelligence, Conflict and Warfare, 2025)
On November 20, 2024, Julia Davis presented Key Takeaways Regarding the Intentions of Russia’s Media Campaigns for this year’s West Coast Security Conference. The presentation was followed by a question-and-answer period with questions from the audience and CASIS Vancouver executives. The key points discussed were Russia’s potent hybrid warfare capabilities, how Russian media acts as an extension of its intelligence apparatus and should therefore be viewed as such, and why the West should view Russian rhetoric with greater caution given that media groups often explicitly outline the State’s broader ambitions.